Pendidikan Entrepreneurship bagi Pengelola Badan Usaha Milik Desa (BUMDes) Mugibangkit - Sri Nathasya Br Sitepu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Entrepreneurship education is given to the manager of the Mugibangkit Village-Owned Enterprise (BUMDes), Munggugianti Kacamatan Benjeng Village, Gresik Regency. The purpose of the activity is to provide entrepreneurship education to improve managerial skills and develop business units at Mugibangkit BUMdes. The implementation of entrepreneurship education activities took place in Munggugianti Village for 12 months. Entrepreneurship education in the form of entrepreneurship theory and practice is divided into four stages of learning including: (1) Exploring the entrepreneurial potential of each BUMDes manager; (2) Transfer of knowledge (entrepreneurship concept); (3) Project-based learning (Preparation of plans for new business units); (4) Mentoring and business evaluation. The results of entrepreneurship education activities: (1) Increasing knowledge of entrepreneurship from 10 managers of BUMDes Mugibangkit; (2) Designing a new business unit (Integrated Tourism Village) in the form of a masterplan which will then be realized into a new business unit at BUMDes Mungibangkit. DOI: https://doi.org/10.26905/abdimas.v6i2.5121